Development and Characterization of Nanobodies Targeting the Kupffer Cell - Zheng, Fang; Zhou, Jinhong; Ouyang, Zhenlin; Zhang, Jiaxin; Wang, Xinyi; Muyldermans, Serge; Van Ginderachter, Jo; Devoogdt, Nick; Wen, Yurong; Schoonooghe, Steve; Raes, Geert (Frontiers in Immunology, 2021)
Nanobodies that are derived from single-chain antibodies of camelids have served as powerful tools in diagnostics, therapeutics and investigation of membrane receptors' structure and function. In this study, we developed a series of nanobodies by a phage display screening building from lymphocytes isolated from an alpaca immunized with recombinant mouse Kupffer cell receptor Clec4F, which is involved in pathogen recognition by binding to galactose and N-acetylgalactosamine. Bio-panning selections retrieved 14 different nanobodies against Clec4F with an affinity ranging from 0.2 to 2 nM as determined by SPR. Those nanobodies mainly recognize 4 different epitopes as analyzed via competitive epitope binning. By analysis of the radioactivity in each organ after injection of 99mTc labeled Clec4F nanobodies in naïve mice, we found that these nanobodies are targeting the liver. Furthermore, we performed a structural characterization at atomic resolution of two of the Clec4F nanobodies from different epitope groups, which revealed distinct features within the CDR2 and CDR3 regions. Taken together, we developed a series of nanobodies targeting multiple distinct recognition epitopes of the Kupffer cell-specific receptor Clec4F which may be useful for its structural and functional investigation as well as for use as molecular imaging and therapeutic agents.